VISUAL ORGANIZERS AS SCAFFOLDING TECHNIQUES IN TEACHING ENGLISH IN NONPHILOLOGICAL UNIVERSITIES - Azizova Gulnora Shakirdjanovna Senior Teacher of the National Institute of Fine Arts and Design named after Kamoliddin Bekhzod, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article is devoted to the methods of teaching a foreign language in non-philological higher education institutions and the problems of language learning. In addition, the article describes the effectiveness of using visual aids. Keywords: Visualization, language, method, skill, technology.